Gestão de reservas florestais: reflexões a partir da floresta estadual do Antimary (AC) - PINTO, Michele de Azevedo (Universidade Federal do Pará, 2018)
The research aim was to analyse the main difficulties and advances within the process of a forest reserve direct management from the case study of Antimary Forest Reserve in Acre. The research examined the factors that contributed to forest management, natural resources conservation and local community development within the conservation unit. The Acre State was a pioneer in establishing a forest policy in Amazonia focussed to promote sustainable development based on the standing forest value. As a form to support this policy the State carried out the State Public Forest Program in order to manage the state forests. This Program has the premise of ensuring natural resources conservation together with the regional and community development. The research theoretical framework was based on the literature of conservation unit, forest management and the influence of the social movement on the sustainable development program in Acre. This framework was used to rebuild the geopolitical context and to understand the processes and results of the unit management.Methodologically, the research was based on qualitative analysis and historical-descriptive method for data assessment. For data collection it was used semi-structured interviews, documentary analysis and geoprocessing tools. The research shows that the direct management of the Antimary State Forest that has been carrying out with external support has failed in ensuring an efficient management of the unit. This fail has happen in spite of the state forest policy advances, the guidelines established in the State Public Forest Program, management tools, management unit plan, advisor council and the positive results emerged to the local communities.